Pillars of Biology: 'The genetical evolution of social behaviour, I and II'. (7th April 2023) - Wild, Geoff
Highlights: I briefly summarize two classic papers by W. D. Hamilton, published in Volume 7 of the journal (in 1964). In this work Hamilton introduced 'inclusive fitness' and I explain why the concept was transformative. I identify three key developments in inclusive-fitness theory since 1964, and I suggest there is scope to develop the theory further.